Polymer/steel Tribological Characteristics and Corrosion and Under External Voltages - Al-Ghamdi, S. A.; Abo-Dief, H.; Mohamed, A. T. (Advanced Aspects of Engineering Research Vol. 11, 2021)
During working, metals are always in contact with its environment whether air, vapor, water, and other chemicals which emerges chemical interactions between metals and their respective environments that resulted in an insidious localized form of corrosion causing much devastating destruction to structural members such as stainless steel in H2SO4 environment. Weight loss experiments, were employed to study the corrosion activity. The present work discusses experimentally the performance of three types of oil-dispersed polymers; low-density polyethylene (LDPE), high-density polyethylene (HDPE) and Polysulphide rubber (PSR) on the abrasive sliding wear of stainless steel. The external voltage increases both friction coefficient and wear scar diameter on which PSR has a lower scar diameter followed by both LDPE and HDPE trends respectively. Negative applied voltage has lower scar diameter compared to the positive applied voltage for all applied polymers. The wear rate trends of HDPE has higher wear rates followed by LDPE and PSR respectively. The metallographic examination showed that the H2SO4 solution interacts with the specimen’s surface causes pitting corrosion and makes it weak, damaged and changes their roughness with immersion time.